Cross Cultural Counseling on Conflict Resolution in Early Children - Sriyati Dwi Astuti; Nurul Qomariah; AgusSriyanto (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2024)
Conflict during a child's development can occur when the child has the awareness that he is part of a group. This conflict arises in interactions between children and requires counseling from adults to be able to teach them how to resolve the conflict. In a multicultural society, conflict resolution can be different. Early childhood children and educators at PAUD Institutions in the city of Pangkalpinang come from various ethnicities including Malay, Chinese, Javanese, Sundanese and Bugis. This research aims to find out the implementation of cross cultural counseling in conflict resolution for children in PAUD in Pangkalpinang City. This research is field research using qualitative descriptive research methods with a cross-cultural counseling theory approach. Data collection was carried out by interviewing 10 educators and observing for two months the learning process from five PAUD institutions in Pangkalpinang City. The results of this research show that educators at PAUD Pangkalpinang have provided integrated cross-cultural counseling with the learning process in TK/RA. In the guidance process, educators understand the values held by students who have different cultures. Educators provide guidance by advising and listening to children about the differences in cultural values that exist in Indonesia.